Fiberglass Reinforced Plastics - Cheremisinoff, N.P. (Noyes Publications, 2011)
This book has been prepared as a reference on manufacturing techniques and applications of fiberglass reinforced plastics. It provides discussion of properties and concepts, and is written for the potential user to summarize advantages in usage.